2017
DOI: 10.1037/xhp0000461
|View full text |Cite
|
Sign up to set email alerts
|

Time contracts and temporal precision declines when the mind wanders.

Abstract: Our perception of time varies considerably from moment to moment, but how this variability relates to endogenous fluctuations in attentional states has been neglected. Here, we tested the hypothesis that perceptual decoupling during spontaneous mind wandering episodes distorts interval timing. In two studies with different visual subsecond interval timing paradigms, participants judged their attentional state on a trial-by-trial basis. Mind wandering states were characterized by underestimation of temporal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Indirect support for this hypothesis comes from a recent survey of microdose users that found that participants reported being more focused on the first day of microdosing (Polito and Stevenson 2018), although this effect declined on subsequent dosing days and it remains unclear whether the self-reported change in attentional focus in the latter study is attributable to a placebo response. Although we are unable to completely discount this interpretation, participants completed the temporal reproduction task on the fourth dosing day and did not report differential concentration under LSD and previous research shows that both phenomenological and behavioural indices of attentional state covary with individual differences in interval timing (Berry et al 2014; Terhune et al 2017).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Indirect support for this hypothesis comes from a recent survey of microdose users that found that participants reported being more focused on the first day of microdosing (Polito and Stevenson 2018), although this effect declined on subsequent dosing days and it remains unclear whether the self-reported change in attentional focus in the latter study is attributable to a placebo response. Although we are unable to completely discount this interpretation, participants completed the temporal reproduction task on the fourth dosing day and did not report differential concentration under LSD and previous research shows that both phenomenological and behavioural indices of attentional state covary with individual differences in interval timing (Berry et al 2014; Terhune et al 2017).…”
Section: Discussionmentioning
confidence: 66%
“…Interval timing is closely intertwined with attention and working memory (Buhusi and Meck 2009; Gu et al 2015; Matthews and Meck 2016), and thus, the present results are plausibly driven by changes in these fundamental cognitive systems. It seems unlikely that the current results can be attributed to poorer working memory or selective attention, such as an increase in attentional lapses, as such effects would have been expected to produce temporal under-reproduction (Buhusi and Meck 2009; Terhune et al 2017; Wittmann et al 2007). An alternative explanation for our results is that microdose LSD enhanced selective attention to duration during the task, resulting in a tendency to over-reproduce temporal intervals (Buhusi and Meck 2009; Lake and Meck 2013).…”
Section: Discussionmentioning
confidence: 85%
“…When MW happens during a task, it moves operators' minds away from their tasks toward matters not directly related to their current works. Although such uncontrolled thoughts could be beneficial as long-term planning and mind refreshment (McMillan et al, 2013;Ottaviani and Couyoumdjian, 2013;Terhune et al, 2017), it may thwart shortterm performances (He et al, 2011;Galera et al, 2012;Cowley, 2013;Casner and Schooler, 2014;DĂŒndar, 2015). Therefore, real-time tracking of MW is an important goal within safetycritical industries, particularly when automation supervision fills a significant part of the job.…”
Section: Introduction Contextmentioning
confidence: 99%
“…Specifically, within-participant variability in the regulatory control between mind wandering and attentional states, or the degree of fluctuations between off-task and on-task processes, may also inform functional outcomes. Research has long determined that attentional abilities fluctuate over the course of a day (Busch and VanRullen, 2010), over the span of an hour (Smallwood et al, 2008;Reichle et al, 2010;Terhune et al, 2017), and even over the span of minutes (e.g., 5 min; Cheyne et al, 2009). Although this evidence is suggestive of a recurrent pattern of attentive and mind wandering behaviors within individuals, the characterization of these variations and their effects on performance remain unknown.…”
Section: Discussionmentioning
confidence: 99%